2003
DOI: 10.1002/ijc.11300
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in cancer mortality in China: 1987–1999

Abstract: A first analysis of time trends in cancer mortality in China at the national level is presented. Using a joinpoint regression model, based on data from a national mortality routine reporting system in China (CHIS), time trends in mortality for 9 major cancers are analyzed. Between 1987 and 1999, the age-standardized mortality rates for all cancers combined declined slightly in rural areas but have increased since 1996 in urban areas. The mortality rates for cancers in oesophagus, stomach, cervix uteri, leukaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
171
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(174 citation statements)
references
References 43 publications
2
171
0
1
Order By: Relevance
“…The remarkable changes in mortality for most major cancers, and their possible explanations have been the subject of an earlier communication (Yang et al, 2003b). The very large improvements in socioeconomic and sanitary conditions may be responsible for declines in cancers associated with infection and/or nutritional deficiency, such as oesophagus, stomach, cervix uteri and nasopharynx, while changes in diet and a more sedentary lifestyle, associated with an increasing prevalence of obesity, may explain some of the changes in risk for cancers of the breast and large bowel.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The remarkable changes in mortality for most major cancers, and their possible explanations have been the subject of an earlier communication (Yang et al, 2003b). The very large improvements in socioeconomic and sanitary conditions may be responsible for declines in cancers associated with infection and/or nutritional deficiency, such as oesophagus, stomach, cervix uteri and nasopharynx, while changes in diet and a more sedentary lifestyle, associated with an increasing prevalence of obesity, may explain some of the changes in risk for cancers of the breast and large bowel.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, it is not the values of the mortality rates in CHIS that have been used to make a national prediction, but the trends Cancer mortality in China, 1991-2005 within strata of age, sex and urban -rural residence. These trends have been examined in detail elsewhere (Yang et al, 2003b), where it was noted that although there had been no changes in the areas covered by the sample during 1991 -1999, there had been important social and demographic shifts within them, with rapid economic development and marked urban -rural migration. These will have influenced the trends observed within the urban -rural samples in addition to changes in exposures to risk factors, early detection and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rates, are on average, three times lower in less developed countries [20,33]. In China, breast cancer incidence is nearly six times lower than in the United States, but the incidence rate has increased substantially from 1987 to 1999 [40]. Shanghai, the largest industrial city on the east coast of China, demonstrated a 40% increase in breast cancer incidence from 1975 (19.6 per 100,000) to 1997 (27.2 per 100,000) [14,33].…”
Section: Introductionmentioning
confidence: 99%
“…However, nationwide mortality surveys show a heterogeneous pattern of cervical cancer risk, with particularly high rates in central rural provinces (Yang et al, 2003a). Furthermore, while cervical cancer mortality appears to have declined considerably in urban China between 1987 and 1999, this is less marked in rural areas (Yang et al, 2003b). A recent study in one such high-risk rural area, Shanxi Province, revealed that 23.6% of women aged 35 -50 years were infected with high-risk HPV types (Zhao et al, 2006).…”
mentioning
confidence: 99%